P185 Natural history of Crohn's disease postoperative recurrence in a referral centre in the era of biologics and therapeutic intensification based on early endoscopic findings. (16th January 2018) - Buisson, A; Cannon, L; Umanskiy, K; Hurst, R D; Hyman, N H; Sakuraba, A; Pekow, J; Dalal, S; Cohen, R D; Pereira, B; Rubin, D T
Abstract: Background: We assessed the prevalence and the risk factors of endoscopic and clinical postoperative recurrence (POR) in the era of biologics and therapeutic intensification based on early endoscopic findings in Crohn's disease (CD). Methods: From a prospectively maintained database, we consecutively enrolled all CD patients who underwent intestinal resection and anastomosis between 2011 and 2016 with colonoscopy at 6 months (6m) and follow-up >6 months. Endoscopic POR was defined as Rutgeerts' Index (RI) ≥i2. Clinical POR was defined as recurrence of symptoms (HBI > 4) leading to hospitalisation or therapeutic intensification after exclusion of other causes of recurrent symptoms. Results: Overall, 316 patients were included (median follow-up 31 months (range 16.0–45.3)): mean CD duration = 11.7 ± 10.8 years, 50.6% female, 11.7% smokers, 22.8% with perianal lesions and 37.6% with prior intestinal resection. The Montreal classification was: L1 = 35.8 %, L2 = 5.7% and L3 = 58.5%, and B1 = 6.3%, B2 = 48.1% and B3 = 45.6%. The rate of endoscopic POR at 6m was 35.8% (i0 = 50.9%, i1 = 13.3%, i2a = 7.0%, i2b = 13.3%, i3 = 8.2%, i4 = 7.3%). In multivariate analysis, >2 anti-TNF prior to surgery (OR = 3.4 [1.2–9.8], p = 0.026), resection length >30 cm (OR = 1.8 [1.1–3.0], p = 0.025) and surgery for refractoriness to medical therapy (OR = 8.6 [1.5–50.5], p = 0.017) were risk factors of endoscopic POR, while female gender (OR = 0.5 [0.3–0.8], p = 0.006), CD duration >10 years (OR = 0.5 [0.3–0.9], p = 0.049) and combination therapy with anti-TNF and immunosuppressive therapies (IS) (OR = 0.4 [0.2–0.8], p = 0.009) decreased this risk. The rate of clinical POR was 9.3% at 1 year and 24.4% at 2 years. In multivariate analysis, prior intestinal resection (HR = 1.6 [1.1–2.4], p = 0.041), >3 biologics before surgery (HR = 2.7 [1.1–6.5], p = 0.031) and RI≥i2 (HR = 2.5 [1.6–3.9], p < 0.0001) were associated with higher risk of clinical POR. Lower risk for clinical POR was found for CD duration >10 years (HR = 0.6 [0.4–0.9], p = 0.037) and post-op combination therapy (anti-TNF + IS) (HR = 0.5 [0.3–0.9], p = 0.028). In patients who did not receive anti-TNF to prevent endoscopic POR and who experienced endoscopic POR (RI ≥ i2) at 6m, starting combination therapy decreased the risk of clinical POR (HR = 0.4 [0.1–0.9], p < 0.05). Conclusions: In our referral centre, the prevalence of endoscopic POR was the lower than historical reporting, suggesting the positive impact of biological therapy. Combination therapy was the most effective approach to prevent and to treat endoscopic POR. This study also provided external validation of the RI (Figure 1).